Pengaruh Program Penyediaan Perumahan Melalui Dinas (PPMD) terhadap Tingkat Kesejahteraan Prajurit TNI AL - Effendi, Arif; Guyana, Daniel; Marsudi, Danang (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Paying attention to the welfare level of soldiers is also an important task in building and maintaining morale and fighting spirit in the military. This study aims to examine the effect of the Service Housing Provision Program (PPMD) on the level of welfare of Indonesian Navy soldiers. The method used is a survey with a simple random sampling technique and data analysis using simple linear regression. The results of the study show that PPMD ​​has a positive and significant influence on the welfare of TNI AL soldiers, with an R Square value of 0.463. These findings show that PPMD ​​can increase the level of welfare of TNI AL soldiers, so efforts need to be made to continue to improve the quality of the PPMD ​​program in providing housing for TNI AL soldiers.